Multicriteria decision model for ranking the performance of remote work activities: Case study in a call center company in Brazil. - da Silva, Aleson Belo; Marques, Amanda Braga; da Costa Junior, João Florêncio; de Souza, Ricardo Pires (Work, 2025)
Background: The world has rapidly experienced a shift in the work environment due to a global need brought about by the COVID-19 pandemic and the recognition of the advantages that remote work presents for companies engaged in processes and customer service. However, not all employees exhibit the same level of adaptation and performance while carrying out their tasks outside the organization's premises. In this scenario, multicriteria decision analysis emerges as a tool to support the decision-making process in prioritizing employees with the best profile for carrying out telecommuting activities. Objective: To create a multicriteria decision model for ranking in the selection of employees for a call center company based in the state of Rio Grande do Norte, Brazil, for remote work from home. Methods: A case study was conducted, incorporating the application of Value-Focused Thinking (VFT), a questionnaire, and the development of the decision model using the FITradeoff method. The choice is based on the concepts of flexible elicitation from the FITradeoff method (Flexible and Interactive Tradeoff). FITradeoff is a method for eliciting scale constants created in accordance with the scope of the Multi-Attribute Value Theory (MAVT). Results: The model was able to provide support information for ranking employees with the best profiles for transitioning from on-site work to remote work, based on consistent prioritization criteria, aiding decision-makers in justifying the chosen selection. Conclusions: It was possible to rank the best profiles for transitioning work arrangements and gain an understanding of how employees perceive remote work.